2008
DOI: 10.1016/j.freeradbiomed.2008.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic-induced malignant transformation of human keratinocytes: Involvement of Nrf2

Abstract: Arsenic is a well-known human skin carcinogen but the underlying mechanisms of carcinogenesis are unclear. Transcription factor Nrf2-mediated antioxidant response represents a critical cellular defense mechanism, and emerging data suggest that constitutive activation of Nrf2 contributes to malignant phenotype. In the present study when an immortalized, non-tumorigenic human keratinocyte cell line (HaCaT) was continuously exposed to environmentally relevant level of inorganic arsenite (100 nM) for 28 weeks, mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
148
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(169 citation statements)
references
References 49 publications
18
148
0
3
Order By: Relevance
“…Cells were maintained as monolayers in a humidified atmosphere containing 5% CO 2 at 37 °C, and culture medium was replaced every 2 d. The HaCaT cell is a spontaneously immortalized human epithelial cell line developed by Boukamp et al 57 For generating arsenic-resistant cells, cells were maintained continuously in medium containing 2.5 μM of As 2 O 3 similarly as described previously. 12 Cells were seeded at 3 × 10 6 cells per 10-mm diameter/dish and maintained in 2.5 μM As 2 O 3 . At passage 23, cells started growing and reached confluency.…”
Section: Cell Line Cultures and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were maintained as monolayers in a humidified atmosphere containing 5% CO 2 at 37 °C, and culture medium was replaced every 2 d. The HaCaT cell is a spontaneously immortalized human epithelial cell line developed by Boukamp et al 57 For generating arsenic-resistant cells, cells were maintained continuously in medium containing 2.5 μM of As 2 O 3 similarly as described previously. 12 Cells were seeded at 3 × 10 6 cells per 10-mm diameter/dish and maintained in 2.5 μM As 2 O 3 . At passage 23, cells started growing and reached confluency.…”
Section: Cell Line Cultures and Treatmentmentioning
confidence: 99%
“…It is well established that when human keratinocyte cell line (HaCaT) is chronically exposed to arsenic trioxide, malignant transformation occurs as evidenced by the formation of highly aggressive squamous cell carcinoma after inoculation into nude mice. 12 To determine a possible functional link between Notch1 downmodulation and arsenic trioxide-induced malignant transformation we analyzed the Notch1 expression in HaCaTtransformed cells after acute re-exposure to As 2 O 3 (see "Materials and Methods"). Surprisingly, arsenic trioxide treatment in HaCaT-transformed cells (HaCaT-R) did not result in Notch1 inhibition, even when cells were treated with the highest dose, 10 μM (Fig.…”
mentioning
confidence: 99%
“…Immortalized cells are needed for chronic exposure studies because it is necessary to maintain these cells are maintained for an extended time required for transformation. Immortalized human keratinocytes (HaCaT) are an in vitro model for normal human keratinocytes that can be used to study arsenic-induced skin cancer (39,64). Pi et al (2008) showed that continuous exposure of HaCaT cells for 28 weeks to a low level (100 nM) of sodium arsenite transformed these cells and resulted in an aggressive SCC phenotype upon inoculation of nude mice (39).…”
Section: Arsenic-induced Skin Cancer Modelsmentioning
confidence: 99%
“…Immortalized human keratinocytes (HaCaT) are an in vitro model for normal human keratinocytes that can be used to study arsenic-induced skin cancer (39,64). Pi et al (2008) showed that continuous exposure of HaCaT cells for 28 weeks to a low level (100 nM) of sodium arsenite transformed these cells and resulted in an aggressive SCC phenotype upon inoculation of nude mice (39). The concentration of 100 nM sodium arsenite was selected based on an epidemiological study of a population in China that consumed well water containing high concentrations of arsenic.…”
Section: Arsenic-induced Skin Cancer Modelsmentioning
confidence: 99%
See 1 more Smart Citation